Continuous delivery with Windows and .NET - Skelton, Matthew; O'Dell, Chris (O'Reilly Media, 2016)
For Windows and .NET developers, Continuous Delivery (CD) is no longer just a theory, but a very practical option. With this concise book, you'll learn how to use modern Windows and .NET software with third-party and open source tools to automate the frequent software builds, testing, and deployments that CD prescribes. Although CD has become a well-defined set of practices and approaches to releasing software in a reliable way, many tools commonly used for CD aren't natively available for Windows. But new and forthcoming features in Windows Server 2016 and Visual Studio 2015 are designed with CD in mind. The tips and advice in this book will help you pursue CD for Windows- and .NET-based software. Specifically, you'll learn about: Version control practices, technologies, and branching options Options for Continuous Integration servers, version control systems, build automation, and package management for Windows and .NET Tools that work well for visualizing and orchestrating a CD deployment pipeline Infrastructure automation, using a test-first approach with Vagrant virtual machines and Microsoft Azure, and--coming soon--Docker for Windows-specific workloads The tricky bits: making changes to your organization and practices beyond adopting the technologies and techniques already discussed.